United States : Financial Sector Assessment Program-Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses the results of the Financial System Stability Assessment on the United States made under the Financial Sector Assessment Program. It is found that welcome steps have been taken in strengthening the financial system. The Financial Stability Oversight Council now provides a useful forum for coordination, the regulatory perimeter has expanded, information sharing among agencies has improved, supervisory stress testing is leading changes in risk measurement and management, and new resolution powers have been established. However, new pockets of vulnerabilities have emerged, partly in response to the continuing search for yield. This requires a continuing focus on strengthening the micro and macroprudential framework.